2015
DOI: 10.1590/0004-282x20150188
|View full text |Cite
|
Sign up to set email alerts
|

Anterior temporal lobectomy versus selective amygdalohippocampectomy in patients with mesial temporal lobe epilepsy

Abstract: Objective To contribute our experience with surgical treatment of patients with mesial temporal lobe epilepsy (mTLE) undergoing anterior temporal lobectomy (ATL) or selective amygdalohippocampectomy (SelAH). Method This is a retrospective observational study. The sample included patients with medically refractory mTLE due to unilateral mesial temporal sclerosis who underwent either ATL or SelAH, at Hospital de Clinicas – UFPR, from 2005 to 2012. We report seizure outcomes, using Engel classification, cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…Finally, 13 studies dealing with MRgLITT [21][22][23][24][25][26][27][28][29][30][31] and six dealing with RFA [32][33][34][35][36] were included (Figure 1). For ATL and sAHE, four RCTs 4,37-39 and 20 comparative studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] were included.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 13 studies dealing with MRgLITT [21][22][23][24][25][26][27][28][29][30][31] and six dealing with RFA [32][33][34][35][36] were included (Figure 1). For ATL and sAHE, four RCTs 4,37-39 and 20 comparative studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] were included.…”
Section: Resultsmentioning
confidence: 99%
“…There were more studies that were included in our meta-analysis compared with prior meta-analyses by Josephson et al 5 and Hu et al 4. In particular, there were seven studies that were not included in prior meta-analyses—Arruda et al ,39 Renowden et al ,48 Tahir et al ,51 Sagher et al ,49 Bujarski et al ,41 Wendling et al 54 and Nascimento et al 46—which demonstrated no significant difference in seizure-free outcome of ATL versus SAH. The inclusion of new data from these studies may have contributed to differences in this study’s conclusion relative to prior meta-analyses.…”
Section: Discussionmentioning
confidence: 97%
“…The studies that have compared neurocognitive outcomes between SAH and TLR are reviewed in Table 3. 33,[37][38][39][49][50][51][52][53][54][55][56] In general, these are small case series or retrospective cohort studies (level 4 evidence).…”
Section: Neuropsychological Outcomesmentioning
confidence: 99%